Application of the Principle of Propotionality in Sentencing for Criminal Acts of Assault - Ahbym Faizan; Abdul Rahman Maulana Siregar; Rahmayanti Rahmayanti (CV. Era Digital Nusantara, 2025)
The principle of proportionality is an important principle in criminal law that serves to ensure a balance between the severity of the crime and the punishment imposed. In crimes of assault in Indonesia, the application of the principle of proportionality is crucial because variations in the form of assault often lead to differences in the level of culpability of the perpetrator and the impact on the victim. This study aims to analyze the application of the principle of proportionality in criminal justice practice, particularly in relation to judges' decisions in assault cases. The method used is a normative juridical approach by examining the provisions of the Criminal Code (KUHP), legal doctrine, and relevant court decisions. The results of the analysis indicate that the application of the principle of proportionality still faces several obstacles, such as disparities in decisions, judges' subjectivity in assessing mitigating and aggravating circumstances, and limited binding sentencing guidelines. Nevertheless, the principle of proportionality remains an important foundation in realizing substantive justice, by considering aspects of victim rights protection, crime prevention, and social reintegration for perpetrators. In conclusion, the application of the principle of proportionality in criminal acts of assault in Indonesia requires consistent application by judges, clearer sentencing guidelines, and strengthening the role of progressive law to achieve a balance between individual and societal interests.